Electrochemical behavior and conversion to Fe2O3 nano particles of a neutral seven coordinated iron(III) complex with dipicolinic acid. Issue 1 (2nd January 2019) - Ahadiat, Ghasem; Tabatabaee, Masoumeh; Gholivand, Khodayar; Zare, Karim; Dušek, Michal; Kučeráková, Monika
Abstract: An iron complex of dipicolinic acid (dipicH2 ), formulated as [Fe(dipic)(NO3 )(H2 O)2 ]·2H2 O (1 ), was prepared and characterized. Cyclic voltammetric response of bare carbon paste electrode surface in 0.10 mol L −1 phosphate buffer containing1 at pH = 7 and at various scan rates (10–70 mVs −1 ) was studied. The apparent charge transfer rate constant, ks, and transfer coefficient, a, for electron transfer [Fe(dipic)(NO3 )(H2 O)2 ]·2H2 O were calculated as 1/1 ± 0.10 s −1 and 0.49, respectively. Thermal decomposition of1 in the presence of polyethylene glycol led to the formation of Fe2 O3 .